ARCHIVAL MATERIAL ABOUT SOCIETIES AND THEIR PERSONALITIES IN THE FIRST HALF OF THE 20TH CENTURY, PRESERVED IN THE WRÓBLEWSKI LIBRARY OF THE LITHUANIAN ACADEMY OF SCIENCES - ILGIEWICZ, HENRYKA (Knygotyra, 2012)
In this paper, a brief overview of the archival materials concerning the Society of the Science and Art Museum (1907–1914), Society of the Library of Eustachy and Emily Wróblewski (1912–1922), Society of Eustachy and Emily Wróblewski Science Fund (1922–1939) and Society of Wróblewski Library Friends (1936–1939) is presented. These materials are kept in the Wróblewski Library of the Lithuanian Academy of Sciences. The first one of the mentioned above societies gathered a valuable collection of rare printed matter and archival documents (the remaining part is kept now in the Wróblewski Library of the Lithuanian Academy of Science); the other three societies have taken part in founding the library and in the proliferation of its funds. After an overview of archival sources, a conclusion is made that the archival material concerning various societies that acted in Vilnius in the first half of the 20th century are of the same character. The majority of them are statutes of the societies, lists of members, the minutes of meetings, activities and financial reports, cash books, statements of inspections and various official papers. These documents enable to restore in essence the circumstances of founding these societies and the main features of their activities. Very valuable is the material in the Manuscript section concerning famous personalities of these societies: Lucjan Uziębło, member of the Vilnius Society of Science and Art Museum, and Tadeusz Wróblewski, the founder of Eustachy and Emily Wróblewski Library. The material comprises their personal documents, scientific certificates, letters, notes, manuscripts, death certificates, obituaries. All this archival material is important not only for the history knowledge of the mentioned societies; it is significant also for the knowledge of the cultural and scientific life in Vilnius of the first half of the 20th century; therefore, it is necessary to preserve it as an important documentary heritage.